Dosimetric comparison of irradiated small bowel volume with intensity modulated radiotherapy and volumetric modulated arc therapy in adjuvant pelvic radiation therapy for endometrial carcinoma - Philip, Maria; Antony, Febin; Chalissery, Jomon Rapahel; Boban, Minu (International Journal of Advances in Medicine, 2023)
Newer treatment techniques help in reducing dose to small bowel (SB) which is an organ at risk (OAR) for pelvic radiotherapy (RT). However, instead of SB, bowel bag is contoured routinely and constraints are given. In this retrospective case series, we compared the dose received by SB while using intensity modulated radiation therapy (IMRT) and volumetric-modulated arc therapy (VMAT) techniques in patients receiving adjuvant pelvic RT for endometrial carcinoma. 10 patients with stage II EC who received VMAT were included in this single institution study. SB was contoured retrospectively in the planning computed tomography scan of these patients. An IMRT plan was also generated with a similar planning target volume coverage and organ at risk (OAR) constraints of the previously approved VMAT plan. Volume receiving 10 Gy, 20 Gy, 30 Gy, 40 Gy and 45 Gy of SB was analysed and a dosimetric comparison was made among the two plans. Anaylysis of variance (ANOVA) and unpaired t tests were used for dosimetric comparison. Mean SB volume receiving 10 Gy (V10 Gy) was 85.3% and 83.7% with IMRT and VMAT respectively. Mean SB volume receiving 45 Gy (V45 Gy) was 4.1% and 5% with IMRT and VMAT respectively. No statistically significant difference was noted in the low dose or high dose irradiated volume of SB using both techniques; however, the volume of SB getting irradiated in the absence of optimisation was found to be high in both the groups which can translate in to acute and late bowel toxicity. Further prospective studies have to be conducted to know the clinical significance of this dose-volume relationship to SB.